Qur'anic Mindfulness Innovation PAI approach in Responding Generation Z 's Mental Health Crisis - Nurkamariah Nurkamariah (Prodi PAI STIT Sunan Giri Bima, 2025)
Crisis Mental health of Generation Z in the era of digital disruption characterized by the phenomena of social comparison and fragmentation soul demand repositioning of Islamic Religious Education (PAI) from just aspect cognitive become instrument psycho -spiritual research This aim For formulating an PAI integration model based on Qur'anic Mindfulness as an intervention strategy mental crisis through method qualitative type studies library research with technique analysis content analysis of literature Islamic psychology and spirituality for the period 2020-2025. Analysis results show that Qur'anic Mindfulness works through the